A multinomial model for the quality control of colony counting procedures - B. Voss; S. Dahms; Joachim Kunert; H. Weiss (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
The so-called good-laboratory-practice (GLP) test provides an experimental design and appropriate statistical analysis for the problem of analyst performance assessment in microbiological laboratories. For a given sample material multiple dilution series are generated yielding colony counts from several dilution levels. Statistical evaluation is based on the assumption of Poisson-distributed colony forming units. In this paper a new model based on conditional binomial and multinomial distributions is presented and it is shown how it is related to the standard model which assumes Poisson-distributed colony counts. The effects of common working errors on the statistical evaluation of the GLP-test are investigated.
Keywords: 519; standardized analytical methods; Good-laboratory-practice-test; Poisson model; multinomial model; quality control